Unforeseen Events Wait Lurking : Estimating Policy Spillovers From U.S. to Foreign Asset Prices - Bayoumi, Tamim (IMF Working Papers; Working Paper, 2011)
Event studies are used to analyze the impact of U.S. financial, fiscal, and monetary policies from US to foreign asset prices across a range of G20 countries and Switzerland. The initial announcement that the Administration supported tighter regulation of banks led to a generalized fall in advanced economy bank shares compared to local equity markets. For later Dodd-Frank announcements, however, falls in U.S. bank equity prices were accompanied by increases in U.K. and Swiss valuations, implying a potential for regulatory arbitrage. Turning to macro policies, the 2008/9 fiscal and monetary stimulus packages generally supported foreign activity, while the impact of similar stimulus in 2010 is less clear.